Sikap Indonesia atas Resolusi Dewan Keamanan PBB terkait Sanksi terhadap Korea Utara - Wulandari Wulandari (STISIPOL Raja Haji, 2026)
United Nations Security Council (UNSC) Resolution 1718 of 2006 imposed sanctions on North Korea due to its nuclearization program. The influence of the geopolitical power of great powers has shaped the global constellation and affected state actions in dealing with North Korea. Despite pressure from the United States, Indonesia has not implemented the UNSC Resolution to impose sanctions on North Korea into its national regulations. As a result, legal ambiguity has arisen regarding the handling of violations committed by North Korea in Indonesian waters. This study aims to reveal the reasons behind Indonesia’s reluctance to implement UN Security Council sanctions against North Korea and its relation to Indonesia’s position as a non-permanent member of the UN Security Council in 2019–2020. By applying Stephen M. Walt’s balance of threat concept, this study concludes that Indonesia chose not to implement UNSC resolutions against North Korea in order to maintain historical and diplomatic closeness with North Korea. Furthermore, although North Korea has demonstrated its military capabilities on several occasions, there have been no statements or offensive and aggressive actions directly directed at Indonesia that could be perceived as a threat. The divided positions of the P5 members during the panel sessions on Resolution 1718 further increased Indonesia’s hesitation in implementing the resolution. As divisions among the P5 continue to deepen, Indonesia needs to reconsider its decision to become a non-permanent member of the UN Security Council for the 2029–2030 term.